Efektivitas Penggunaan Media Alat Peraga “Perahu Rakit” dan Laboratorium Maya pada Materi Hukum Archimedes - Zahro, Fatimatuz; Tri Suci Ambarwati; Septianingrum, Jijah; Subekti, Hasan; Mahdiannur, Muhamad Arif (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2022)
The learning Media used today is sophisticated because it utilizes information technology. However, simple teaching aids still remain relevant in science learning. The purpose of this study is to determine the validity of the props that have been made, namely props "boat raft" in the application of Archimedes law. Testing the validity of the props also made use of virtual laboratory simulation "Archimedes law" on the site of Virtual Lab, home of learning. The research method used in this study is design-research by utilizing small-scale Class Trials. Data processing in determining validity using Aiken's coefficient V. The validity of props according to two science teachers is more effective in virtual laboratory simulation of "Archimedes law". Interest and motivation of students while learning the majority respond interesting and easy in the use of raft boat props. The students ' responses to the media props test the effectiveness of the raft boat props in terms of design aspects, aspects of quality and aspects of effectiveness. The results obtained indicate that the virtual laboratory simulation “Archimedes law” has the potential to increase motivation and interest in learning in students.